2010
DOI: 10.1007/s00726-010-0706-0
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcylation of the Plum pox virus capsid protein catalyzed by SECRET AGENT: characterization of O-GlcNAc sites by electron transfer dissociation mass spectrometry

Abstract: The capsid protein of Plum pox virus (PPV-CP) is modified with O-linked β-N-acetylglucosamine (O-GlcNAc). In Arabidopsis thaliana this modification is made by an O-GlcNAc transferase named SECRET AGENT (SEC). Modification of PPV-CP by SEC is hypothesized to have a direct role in the infection process, because virus titer and rate of spread are reduced in SEC mutants. Previous studies used deletion mapping and site-directed mutagenesis to identify four O-GlcNAc sites on the capsid protein that are modified by E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 23 publications
3
30
0
Order By: Relevance
“…The OGT activity of SEC has been demonstrated (Kim et al, 2011), and a recent study by Zentella et al (2016) showed that SEC interacts with and O-GlcNAcylates DELLAs, reduces their activity, and promotes GA responses. SPY, similar to SEC, contains multiple tetratricopeptide repeats at the N terminus, which bind substrate proteins, and a putative OGT catalytic domain at the C terminus (Silverstone et al, 2007).…”
mentioning
confidence: 98%
“…The OGT activity of SEC has been demonstrated (Kim et al, 2011), and a recent study by Zentella et al (2016) showed that SEC interacts with and O-GlcNAcylates DELLAs, reduces their activity, and promotes GA responses. SPY, similar to SEC, contains multiple tetratricopeptide repeats at the N terminus, which bind substrate proteins, and a putative OGT catalytic domain at the C terminus (Silverstone et al, 2007).…”
mentioning
confidence: 98%
“…Proteins from the fucta/fuctb/xylt triple mutant were treated with PNGase F and digested with endo-Lys-C or trypsin. Peptides bearing modifications with terminal GlcNAc were then enriched by lectin affinity chromatography (Kim et al, 2011). In this procedure, terminal GlcNAc is enzymatically capped with Gal using bovine b-1,4-galactosyltransferase, creating the disaccharide N-acetyl-D-lactosamine (LacNAc).…”
Section: Arabidopsis Proteins Can Be Modified With An N-glcnacmentioning
confidence: 99%
“…O-GlcNAc-modified CT-5 was prepared by coexpressing it with SECRET AGENT as described previously (Kim et al, 2011). Detection of GlcNAcylated proteins on the blots was performed as described (Kim et al, 2011).…”
Section: Recombinant Protein Preparation and Detection Of Glcnacylatementioning
confidence: 99%
See 2 more Smart Citations